Untersuchungen zur jungtertiären Flächenbildung, Verwitterung und Klimaentwicklung im südöstlichen Taunus und in der Wetterau - Bibus, Erhard (ERDKUNDE, 1973)
Starting from the findings of other workers, the author presents as a result of his research in the southeastern periphery of the Rhine Massif, a contribution to the question of weathering and the formation of flattened levels in the late Tertiary. The levels were not formed as a result of valley filling but by continual, phased, incision processes with transport of residual debris over largely decomposed rock. The autochthonous weathering relicts preserved on the levels differ from fresh rock in their high rate of kaolinite re-formation, SiO2 enrichment and their Fe and Al losses. Pedological, claymineralogical and chemical investigations showed, for a weathering profile on Devonian clay slates and Middle Upper Miocene basalt, that deep-reaching, lateritic weathering was possible in the late Tertiary. The data were confirmed by several deep borings and could be extrapolated on a supra-regional basis. A weathering-intensive and at least occasionally damp and warm subtropical climate must be regarded as the context for the creation of late Tertiary paleosoils. Appropriate conditions can - in spite of some objections - be shown to have existed in the study area on the basis of paleobotanical investigations. The results reported here stand in partial contradiction to the opinions of J. Birkenhauer (1970/ 1971) a fact which becomes clear in a closing comparison.